Factors affecting customers’ retention towards sale of petrol & diesel : a case study of Sukimi (M) Sdn Bhd / Wan Noorismaryani Ismail - Ismail, Wan Noorismaryani (2012)
The aim of this study was to examine the factor that affecting customer’s retention towards sales of petrol and diesel at Sukimi (M) Sdn Bhd. In this study, researcher has chosen customer loyalty, customer relation and sales promotion as independent variable, for the dependent variable researcher has chose customers' retention. This study also was conducted what are the most preferred factor that influence customer retention towards sales of petrol and diesel at Sukimi (M) Sdn Bhd. Moreover questionnaire had been use in order to get feedback from customer. Researcher had distributed 100 questionnaires to Sukimi (M) Sdn bhd customer at area Kelantan. Then the researcher analyzed the data from questionnaires using Statistical Package for Social Science 16.0 Students Version. Data was interpreted and test using frequency distribution analysis and then further analyzed using Reliability analysis. Frequency distribution analysis was used to shows the statistics displays to describe the variables. The researcher also presents the reliability analysis table to shows the relationship between the dependent variable and independent variables which is all variable are very reliable and acceptance. Correlation analysis used to test hypotheses. The results show that all three independent variables have positive relationship with dependent variables. In terms of regression analysis, the most affecting customers’ retention is customer loyalty but the customer relation and sales promotion are not significant. Besides, some recommendation and suggestion depending on the result based on the analysis that has been done in the previous chapter. The suggestion will help Sukimi(M) Sdn Bhd to increase their customers' retention towards sales of petrol and diesel. By conducting this research also, the researcher hopes that Sukimi (M) Sdn Bhd can upgrade their performance level in order to make sure that they can stay on the market effectively and at the same time can solve the problem that will occur in the future